2007
DOI: 10.1126/science.1145528
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Neon and Argon Isotopic Fractionation in Solar Wind

Abstract: To evaluate the isotopic composition of the solar nebula from which the planets formed, the relation between isotopes measured in the solar wind and on the Sun's surface needs to be known. The Genesis Discovery mission returned independent samples of three types of solar wind produced by different solar processes that provide a check on possible isotopic variations, or fractionation, between the solar-wind and solar-surface material. At a high level of precision, we observed no significant inter-regime differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 21 publications
8
44
0
Order By: Relevance
“…Xe ratio compares well with 9.9 ± 0.3 given by Vogel et al (2011). Vogel et al (2011 reported an average ratio 36 Ar/ 38 Ar = 5.50 ± 0.01 which also agrees well with a ratio 5.501 ± 0.005 of Meshik et al (2007). Reported ratios 86 Kr/ 84 Kr = 0.303 ± 0.001 and 129 Xe/ 132 Xe = 1.06 ± 0.01, at this time the only values available from Genesis, are consistent with solar data as observed in early etch steps in lunar ilmenite samples (Wieler and Baur, 1994).…”
Section: Stellar Synthesis Products In Heavy Elementssupporting
confidence: 75%
“…Xe ratio compares well with 9.9 ± 0.3 given by Vogel et al (2011). Vogel et al (2011 reported an average ratio 36 Ar/ 38 Ar = 5.50 ± 0.01 which also agrees well with a ratio 5.501 ± 0.005 of Meshik et al (2007). Reported ratios 86 Kr/ 84 Kr = 0.303 ± 0.001 and 129 Xe/ 132 Xe = 1.06 ± 0.01, at this time the only values available from Genesis, are consistent with solar data as observed in early etch steps in lunar ilmenite samples (Wieler and Baur, 1994).…”
Section: Stellar Synthesis Products In Heavy Elementssupporting
confidence: 75%
“…The inspiration for Genesis was the Apollo Solar Wind Composition (SWC) foil experiments (18) which showed that the 20 Ne∕ 22 Ne ratio in the terrestrial atmosphere was 38% lower than that in the solar wind. Genesis has confirmed this important result with higher precision (6,19), and more importantly, extended the documentation of differences between the solar wind and terrestrial atmosphere to the other noble gases. Fig.…”
Section: Science Resultssupporting
confidence: 54%
“…Comparison of various data for solar wind Ar isotopic composition compared to that of terrestrial atmosphere (air). The Genesis data (6,19) have error bars smaller than the symbol size and provide a precise measure of the Ar fractionation of the terrestrial atmosphere that could not be obtained from Apollo SWC data. The necessity of sample return to measure relatively small but important differences is illustrated by comparison with the Soho spacecraft instrument analysis (22) ferences from large fractionations between the Sun and all kinds of solar wind.…”
Section: Science Resultsmentioning
confidence: 99%
“…We suggest using this value as a best current estimate for the average SW-36 Ar flux observed by Genesis. Given this new measure of the 36 Ar flux and 20 Ne flux from Mabry et al (2007) and Meshik et al (2007), the SW 20 Ne/ 36 Ne becomes ~56.5, closer to 51.5 ± 0.5 (Pepin et al, 2012) than to 43.2 ± 0.4 (Heber et al, 2009). The value of SW 20 Ne/ 36 Ne remains one of the major interlaboratory disagreements for Genesis SW compositions.…”
Section: Solar Wind Flux Of Heavy Noble Gasesmentioning
confidence: 82%